5PSQ-122 COVID-19 vaccine vigilance: comparative study between hospital, regional and national data. Issue 1 (23rd March 2023) - Bartolucci, I; Monti Guarnieri, N; Garzone, AMF; Andresciani, E; Bagagiolo, S; Cocci, E; Polidori, C; Pompilio, A
Abstract : Background and Importance: Following AIFA's authorisation of first mRNA vaccine on 27/12/2020, COVID-19 vaccination campaign started in Italy together with vaccine vigilance in order to individuate expected and unexpected Adverse-Events-Following-Immunisation (AEFIs) and the benefit/risk balance. Aim and Objectives: The aim of this work is comparing reports of vaccine vigilance in our Hospital from December 2020 to June 2022 to national and regional data. Material and Methods: Starting from data of the National System of Pharmacovigilance (RNFV), we analysed reports by age, sex, severity of reaction, reporter and System-Organ-Class (SOC) involved (Meddra classification system). Finally, we compared results with twelfth vaccine surveillance report published on June 2022 by the Italian Agency of Drugs (AIFA) and to 2021 annual regional report. Results: In the period our Hospital administered about 111000 doses (99%Comirnaty, 0.3%Vaxzevria, 0.6%Spikevax). 176 reports were collected: 69(39%) concerned Covid vaccination (reporting-rate RR0, 06%). 52(75, 4%) of Covid-reports were not severe and 17(24, 6%) were severe; among those severe, 2 cases of ineffective vaccination (Comirnaty), 1 case of heart attack (Spikevax), 1 case of adrenal hematoma (Vaxzevria) and 1 episode of deep vein thrombosis (Comirnaty). 59 (85, 5%) involved women and 10(14, 5%) men. 65 (94, 4%) involved Comirnaty (23% severe, and further 9% of severe reaction are given by association with other drugs, RR0, 06%), 2 (2, 9%) Spikevax (50% severe, RR0, 6%), 2 (2, 9%) Vaxzevria, (50% severe, RR0, 3%). 216 AEFIs were collected; 83 (38%) general diseases and conditions related to site of injection (13 fever, 9 asthenia); 37 (17%) nervous system diseases (26 headache); 30 (14%) generalised muscular pains (8 myalgia). Little percentage involved also vision, skin and respiratory system. 49% of reports were from doctors, 30% from pharmacists, 15% from other health worker and last 6% patients. 35 (51%) AEFIs were from first dose, 32 (46%) from second and 2 (3%) form third. Almost all reports involved age range 18-64. Conclusion and Relevance: Results on Comirnaty are in line with AIFA's and regional ones; Spikevax and Vaxzevria show altered percentage because of little number of reports. Reporting rates are comparable. Most of reports concerned not severe reactions, mainly related to site of injection. It is important to underline the essential role of vaccine vigilance to identify red flags for public health in order to contain main severe reactions. References and/or Acknowledgements: Conflict of Interest: No conflict of interest